Regulatory oversight of cell therapy in China: Government's efforts in patient access and therapeutic innovation. (August 2020) - Wu, Weijia; Wang, Yuanyuan; Tang, Zhijia; Gao, Yuan; Huo, Yan
Graphical Abstract: Stem cell therapy currently follows a "dual-track" regulatory scheme. On the one hand, pharmaceutical companies can obtain market authorization for a stem cell therapy from the national medical products administration (NMPA) based on evidence from clinical trials. On the other hand, medical institutions can conduct clinical research of stem cell therapies. The draft of the MSCT 2019 introduced the clinical research and application for somatic cell therapy, which, together with market authorization from the NMPA, would also constitute a "dual-track" regulatory scheme. Unlike in the "dual-track" regulatory scheme for stem cell therapies, somatic cell therapies in clinical application could be directly applied to patients. Abstract: In recent years, remarkable progress has been made in the fundamental research and on clinical development of cell therapy. Although China has launched a series of regulations to establish a proper regulatory framework that facilitates the development of cell therapy products, the regulatory framework has not been able to meet the country's regulatory requirements. This article introduced the development of regulation and current regulatory pathways for cell therapy in China and identified the main challenges in clinical studies. China has recently tightened its policy on cell therapy clinical studies after medical chaos occurred in the area of cell therapy over the past few years. Currently the regulatory jurisdiction between NMPA and NHC are not very clear, especially for clinical somatic cell research, further efforts are necessary to establish a legislative system with a clear and functional regulatory framework for cell therapy.